Blunt versus penetrating trauma: differences in early physiology, coagulopathy, and outcomes in a Scandinavian trauma centre - Erik von Oelreich; Jesper Eriksson; Bjarni Arnason; Daniel Ohlén; Axel Hedin; Anders Gille; Malin Jonsson Fagerlund; Magnus Hedberg (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2026)
Abstract Background Blunt and penetrating trauma differ in injury patterns, management, and outcomes, but data comparing early physiological and haemostatic responses within Scandinavian trauma systems remain limited. We aimed to investigate differences in clinical characteristics, early physiology, and outcomes between blunt and penetrating trauma patients at a major Swedish trauma centre. Methods This registry-based observational cohort study included adult trauma patients admitted to the Karolinska University Hospital, Stockholm, between November 2022 and December 2024. Detailed prospective data were collected for patients receiving blood transfusion within two hours of arrival. Patients were categorised by injury type (blunt vs. penetrating). Clinical outcomes included 30-day mortality, hospital length of stay, and functional outcome. Secondary analyses compared physiological, metabolic, and coagulation parameters. Multivariable logistic regression was used to compare 30-day mortality between groups, adjusted for age, sex, Injury Severity Score, and preinjury comorbidity. Results A total of 2,193 patients were included, of whom 353 (16%) sustained penetrating trauma. Patients with penetrating trauma were younger (median 34 vs. 49 years, p < 0.001), more often male (78% vs. 66%, p < 0.001), and more frequently presented in shock (5.9% vs. 2.2%, p < 0.001), with a greater need for emergency surgery (53% vs. 30%, p < 0.001) and early blood transfusion (20% vs. 4.5%, p < 0.001). Blunt trauma patients had higher injury severity (median ISS 10 vs. 4, p < 0.001), longer hospital stays (> 7 days: 26% vs. 18%, p = 0.001), and worse functional outcomes at discharge (Glasgow Outcome Scale 2 or 3: 40% vs. 12%, p < 0.001). In the early transfusion subgroup (n = 152), blunt trauma patients exhibited lower fibrinogen levels (median 2.1 vs. 2.5 g/L, p = 0.027), lower platelet counts (median 239 vs. 271 10⁹/L, p = 0.011), and prolonged activated partial thromboplastin time (median 26 vs. 23 s, p < 0.001) compared with penetrating trauma patients, despite similar rates of trauma-induced coagulopathy defined by INR > 1.2 (23% vs. 16%, p = 0.32). After exclusion of non-trauma-related deaths, 30-day mortality did not differ significantly between groups in unadjusted or adjusted analyses. Conclusions Within this Scandinavian trauma system, blunt and penetrating trauma represent distinct clinical entities with differing injury patterns, physiological responses, and management needs. Despite these differences, adjusted mortality was comparable. These findings may support mechanism-specific assessment and prioritisation in trauma management. Trial registration This study is a secondary analysis of a prospectively registered observational trauma cohort (ClinicalTrials.gov NCT05573841, registered 6 October, 2022).